Remotely supported prehospital ultrasound: A feasibility study of real-time image transmission and expert guidance to aid diagnosis in remote and rural communities. (October 2018) - Eadie, Leila; Mulhern, John; Regan, Luke; Mort, Alasdair; Shannon, Helen; Macaden, Ashish; Wilson, Philip
Introduction: Our aim is to expedite prehospital assessment of remote and rural patients using remotely-supported ultrasound and satellite/cellular communications. In this paradigm, paramedics are remotely-supported ultrasound operators, guided by hospital-based specialists, to record images before receiving diagnostic advice. Technology can support users in areas with little access to medical imaging and suboptimal communications coverage by connecting to multiple cellular networks and/or satellites to stream live ultrasound and audio-video. Methods: An ambulance-based demonstrator system captured standard trauma and novel transcranial ultrasound scans from 10 healthy volunteers at 16 locations across the Scottish Highlands. Volunteers underwent brief scanning training before receiving expert guidance via the communications link. Ultrasound images were streamed with an audio/video feed to reviewers for interpretation. Two sessions were transmitted via satellite and 21 used cellular networks. Reviewers rated image and communication quality, and their utility for diagnosis. Transmission latency and bandwidth were recorded, and effects of scanner and reviewer experience were assessed. Results: Appropriate views were provided in 94% of the simulated trauma scans. The mean upload rate was 835/150 kbps and mean latency was 114/2072 ms for cellular and satellite networks, respectively. Scanning experience had a significant impact on time to achieve a diagnostic image, and review of offline scans required significantly less time than live-streamed scans. Discussion: This prehospital ultrasound system could facilitate early diagnosis and streamlining of treatment pathways for remote emergency patients, being particularly applicable in rural areas worldwide with poor communications infrastructure and extensive transport times.